2020
DOI: 10.1038/s41598-020-75249-5
|View full text |Cite
|
Sign up to set email alerts
|

Asian citrus psyllid adults inoculate huanglongbing bacterium more efficiently than nymphs when this bacterium is acquired by early instar nymphs

Abstract: The Asian citrus psyllid (Diaphorina citri) transmits the bacterium ‘Candidatus Liberibacter asiaticus’ (CLas), which causes huanglongbing (citrus greening) disease, in a circulative-propagative manner. We compared CLas inoculation efficiency of D. citri nymphs and adults into healthy (uninfected) citron leaves when both vector stages were reared from eggs on infected plants. The proportion of CLas-positive leaves was 2.5% for nymphs and 36.3% for adults. CLas acquisition by early instar nymphs followed by dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…For D. citri-citrus-Ca. Liberibacter asiaticus, such threshold is not applicable because studies have shown low transmission associated with a single D. citri adult [11] and even more when nymphal development occurs in healthy plants [9,13,67]. Furthermore, there are diverse natural enemies contributing to the reduction in the vector population [68][69][70][71] that would potentially and naturally assist the prevention of the vector from reaching efficient transmission levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For D. citri-citrus-Ca. Liberibacter asiaticus, such threshold is not applicable because studies have shown low transmission associated with a single D. citri adult [11] and even more when nymphal development occurs in healthy plants [9,13,67]. Furthermore, there are diverse natural enemies contributing to the reduction in the vector population [68][69][70][71] that would potentially and naturally assist the prevention of the vector from reaching efficient transmission levels.…”
Section: Discussionmentioning
confidence: 99%
“…[3,4,6,7]. Characteristically, CLas is transmitted by the Asian citrus psyllid (ACP) Diaphorina citri Kuwayama (Hemiptera: Liviidae) [1,5,[8][9][10]. ACP adults that developed on infected trees were positive for CLas at a rate of 68%, while those that developed on healthy plants were positive at a rate of only 5% [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, the CLam species is dominant, while CLas occurs globally in many citrus growing countries (Hall et al, 2013;Wang et al, 2017a,b;Ammar et al, 2020b). The pathogens replicate and circulate systemically in both the plant and the psyllid host tissues (Ammar et al, 2011(Ammar et al, , 2016(Ammar et al, , 2020aCoy et al, 2014;Ramsey et al, 2015;Kruse et al, 2017Kruse et al, , 2018, which facilitates their effective, rapid spread and persistence (Inoue et al, 2009;Ebert, 2019;Jiang et al, 2019;Huang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…CLas was also demonstrated to alter the host plant transcriptional profile [ 23 25 ]. We also learned CLas infects salivary glands and the midgut of vectors, tissues that are often recognized as natural barriers to circulative, propagative pathogens as they can prevent translocation of pathogens within the vector host [ 17 , 22 , 26 , 27 ]. Differential gene expression analysis of CLas-infected psyllids also demonstrated CLas alters the gene expression profile of of the gut, salivary glands and whole-body of D. citri [ 19 , 28 – 30 ].…”
Section: Introductionmentioning
confidence: 99%